Dinamika Usahatani Kentang di Desa Margamulya, Kecamatan Pangalengan - Daneswara, Naufal; Fatimah, Sri (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Potatoes are the world's fourth largest staple food after wheat, rice, and maize. In Indonesia, potato farming holds great potential, especially in highland areas like Pangalengan, West Java. However, despite the increasing demand for potatoes, production remains insufficient. The high production costs have led many potato farmers in Margamulya Village, Pangalengan Subdistrict, to switch to other commodities. This research aims to identify the farmers who continue to grow potatoes and examine their farming systems. The study employs a qualitative approach with a case study method, as defined by W. Creswell (2020), focusing on understanding individuals or groups' perspectives on social or human issues. The remaining potato farmers in Margamulya Village are considered to be in their productive age, possessing physical strength and openness to innovation. Most of them have received a high level of education, with many holding bachelor's degrees. These enduring potato farmers have inherited the tradition of potato cultivation and boast strong networks and substantial capital. Their motivation to grow potatoes is high, often described as being "passionate" about potato farming. While their cultivation techniques align with guidelines, they do not strictly adhere to good agricultural practices.